Facebook as a source of social connectedness in older adults. (January 2017) - Sinclair, Tara J.; Grieve, Rachel
Abstract: This study examines for the first time whether —and subsequently the extent to which— social connectedness can be derived from Facebook in a population of older Facebook users. Participants ( N  = 280) were aged between 55 and 81 years ( M age  = 61.28 years). Exploratory factor analysis (maximum likelihood with direct oblimin rotation) revealed that Facebook social connectedness emerged as a separate factor to offline social connectedness, with correlations between the factors indicating that they were distinct constructs. In addition, participants reported levels of Facebook-derived social connectedness similar to those seen in younger samples in previous research. Future directions for research include identifying the mechanisms by which Facebook social connectedness might be associated with positive outcomes in older populations. Given the global rate of population ageing, these findings have important implications in terms of the delivery of social capital in older adults. Highlights: Older adults are increasingly using social networking sites such as Facebook (FB). We investigate whether older adults can derive social connectedness from FB. FB social connectedness emerges as a distinct construct. Levels of FB social connectedness were similar to those seen in younger samples. FB is a potential source of social capital in older adults.